The Importance of Antimicrobial Strategies Associated with Clinical Cure and Increased Microbiological Eradication in Patients with Complicated Urinary Tract Infections and High Risk of Relapse - José Medina Polo; Jose Luis Alfonso Sánchez; Jorge Arca-Suárez; Ángel Estella; Pablo González; Martí Blasco; Alicia Gil; Leonor del Mar Periañez Párraga; Francisco Javier Membrillo de Novales (European Urology Open Science)
Background and objective: Complicated urinary tract infections (cUTIs) are serious, potentially life-threatening infections that occur in patients with an increased disease progression risk. Antimicrobial resistance represents an important health issue worldwide, contributing to relapses, which can generate further resistances. It is necessary to clarify the role of microbiological eradication as an additional objective in the management of cUTIs. Some publications suggest that relapses relate to insufficient bacterial suppression in the urinary tract. This study focuses on generating a consensus on how patients with cUTIs would benefit from effective antimicrobial agents associated with higher rates of bacterial eradication. Methods: The nominal group technique was followed: systematic literature review, development of a questionnaire, expert panel meeting to discuss results, individual review of draft consensus document, and expert panel meeting to discuss final views and finalise the consensus document. Key findings and limitations: Experts identified risk factors for cUTIs (patients with a higher risk of relapse, physiological obstruction of urinary tract, immune suppression, and previous relapse), and patients who would benefit most from a therapeutic strategy combining clinical cure and aim for microbiological eradication. While experts agreed that the scientific evidence discourages repetition of urine cultures after treatment, they proposed recommendations to prioritise antibiotics with higher evidence of microbiological eradication and close follow-up in patients with a higher risk of relapse, considering any symptoms appearing following clinical cure of the cUTI. Conclusions and clinical implications: Selection of active antimicrobial agents associated with increased microbiological eradication should be prioritised in patients with cUTIs and a high risk of relapse. Patient summary: Complicated urinary tract infections (cUTIs) occur in patients with an increased risk of disease progression or are caused by multidrug-resistant uropathogens. Antimicrobial resistance is of concern as it can result in relapses. Antimicrobial therapeutic strategies associated with increased microbiological eradication in cUTI patients with a high risk of relapse are crucial to prevent relapses and development of antibiotic resistance.